2018
DOI: 10.3390/ijerph15091972
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Mobile Internet-Based Health Services on Patient Satisfaction and Word-of-Mouth

Abstract: With the rapid advancement of Web 2.0 technologies, Internet medicine, and mobile healthcare, the influence of the use of patient-oriented Mobile Internet-based Health Services (MIHS) on patient satisfaction and the electronic word-of-mouth (WOM) of health service agencies is becoming the focus of the academic research community. Many large hospitals, including some Internet hospitals, have provided various online healthcare service platforms that enable patients to expediently consult with physicians and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 91 publications
1
36
0
Order By: Relevance
“…Lu and Wu researched and confirmed the positive impact of other patients' online service quality assessment on patients' choices [18]. Gu demonstrated through empirical research that patient satisfaction with OHP is positively affected by perceived usefulness and OHP performance expectations [19]. Based on the unified theory of technology acceptance and use, Sun and Lu used SEM to verify the performance expectations, social influence and credibility of network health information are the key factors that affect users' acceptance and use of OHP [20].…”
Section: Commission On Doing a Good Job In Internet Diagnosis And Conmentioning
confidence: 79%
“…Lu and Wu researched and confirmed the positive impact of other patients' online service quality assessment on patients' choices [18]. Gu demonstrated through empirical research that patient satisfaction with OHP is positively affected by perceived usefulness and OHP performance expectations [19]. Based on the unified theory of technology acceptance and use, Sun and Lu used SEM to verify the performance expectations, social influence and credibility of network health information are the key factors that affect users' acceptance and use of OHP [20].…”
Section: Commission On Doing a Good Job In Internet Diagnosis And Conmentioning
confidence: 79%
“…One of the key strategic directions of this system is to engage patients to make better decisions about their health. In academia, researchers have demonstrated that patient participation plays a non-negligible role in enhancing healthcare service, including the nurse–patient relationship, shared decision making, chronic disease treatment, and a redesign of healthcare systems [6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…At this time, a doctor’s online reputation is particularly important. As a signal of a doctor’s medical service level, the doctor’s online reputation provides a decision-making basis for patients to register online [ 19 , 20 , 21 ]. Many studies have confirmed the influence of brand on the sales volume of goods or the purchase intention of consumers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%